A case of liver injury and pneumo-haemoperitoneum during pericardiocentesis. Issue 2 (6th February 2022) - Whiley, Phillip J; Rodrigues, Nicole; Balasooriya, Janaka
Abstract: Pericardiocentesis is a generally safe procedure that provides effective resolution of cardiac tamponade. Emergency pericardiocentesis may be a life-saving intervention. Encountering an intra-abdominal organ in the path of the needle is predicted to be a potential complication in emergency subxiphoid approaches. Despite predictions of intraabdominal injuries, only few instances are recorded. In this case study, a patient recovering from percutaneous cardiac intervention required an emergency pericardiocentesis that was complicated by a liver injury, diaphragmatic penetration and pneumo-haemoperitoneum requiring surgical intervention to remove the drain. The case discusses options for performing the procedure, patient factors that can complicate the procedure and radiological and surgical diagnosis and treatment of this rare event.